Redesign of the science interpretation laboratory application (Labtafsin 2.0) using 3 languages as supporting media for science learning based on Al-Qur'an interpretation - Rifaannudin, Mahmud; Sylvia Puspitasari, Niken; Muryatmoko, Dihin; Bagir Alfahmi, Haidar; Al-Faritzi, Muhammad Redho (Jurnal Inovasi Teknologi Pendidikan, 2024)
The application of the Science Interpretation Laboratory, as a learning media for the development of science interpretation science that leads to an Islamic worldview, faces practical obstacles by often experiencing errors (force close) in its use. This study aims to evaluate and redesign the Science Interpretation Laboratory Application to overcome these obstacles. With the stages of research (Waterfall System Development Life Cycle) SDLC has five stages: Requirements analysis, System and software design, Integration and system testing, and operation and maintenance. Then the application was tested with 2 material and media experts and 38 students.  The results show that the redesign of the Labtafsin 2.0 application was successful, adding 3 language features (Arabic, English, and Indonesian). The functionality test (black box) results show that the application runs smoothly and can be used optimally on Android version 10. Ratings from material experts give an average of 94%, indicating that this app is suitable as a learning resource. Ratings from media experts give an average of 90%, the application is rated as very satisfactory. Then the assessment from students showed a score of 93%, and this application can be used very well. Further, it is necessary to develop, by adding video and quiz features according to the material to support learning.